Verbal Phenomenal Between Perspective And Expectancy - Abdulsattar Salih Ahmed Albanna (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Arabic language is one of the derivational languages which have linguistic features. Among them is the feature of verbal with its structure, grammar and semantic which occupied great space among its founders. Verb is one of the basic elements of the structure of the sentence. In this respect, Arabic expression was the main concern of both ancient and modern authors which hold the attentions and concentrations of the scientists. Dr. Ibrahim Ahmed was one of the scientists who focused on the linguistic aspects. Within his studies, he tackled with the linguistic structure in his researches, essays and books. To reflect this realistic view, we will present verb in its contents (semantic, grammar and derivation) throughout this research paper. The title of this paper is verbal phenomenal between perspective and expectancy which consists of three sections with an abstract. We try to show what is the practical value and approach of Al Samurai?. Section one deals with verb between (Occurrence and Stabilization). While the second section presents the oldness of verb in Arabic between (Being and Quality). Third section highlights the structure between nominal and verbal clues from the point view of Al-Samurai. The research is descriptive one which follows the ideas and opinions in a critical way that the ancients had refused while the modernists were debating. The results show that AL-Samurai sided with the modernists upon the ancients in the concept of attribution. Whereas he was rejecting the ancients in the sense of tense and conditions. In this respect, he supported the ideas of the ancients upon the modernists concerning the problem of rehabilitating time and actually coupling it to the Arabic verb for instance the structure of the sentence and the priority of the verb clues on noun clues in Arabic. The research ends with conclusion